Public participation model for public information disclosure - Ahmadi, Dadi; Rachmiatie, Atie; Nursyawal (Penerbit Universiti Kebangsaan Malaysia, 2019)
Democratic governance is characterized by participation or community involvement in decision-making and implementation of public policy. Relating to community participation, the Indonesian government has a policy for citizens to access information they required. As the effect of this policy, Indonesia has made efforts to implement the disclosure of information in accordance with the freedom of information act. This article aims to build model of public participation from the community to control the region government with case “Wakca Balaka Advocacy Forum” and “Kelompok Informasi Masyarakat (KIM)” in the context of public disclosure. The method used was case study and the data were collected through interviews and discussion forum with Wakca Balaka and observation on KIM activities in Bandung, Indonesia. The results of the research showed that Wakca Balaka Advocacy Forum is a bottom up public participation model, due to its own initiative to oversee various local government policies in its implementation. In addition, "KIM” is a "pseudo" public top down participation model, because it is formed and initiated by the government to manage information and empower the community. This makes KIM have a lower critical level in comparison with Wakca balaka in government transparency. For this reason, capacity building for information management officials in the local government and the Information Commission as regulators are needed, and so is building public awareness about the importance of public participation.